Peran Orang Tua dalam Menumbuhkan Minat Baca Anak Usia 5-6 Tahun - Nur Lailatul Fitri; Hulailah Istiqlaliyah (Universitas Al-Hikmah Indonesia, 2021)
Reading occupies an important position in the context of life, especially in the era of information and technology as it is today. Reading habits from an early age will enrich children's insight which leads to a higher quality human identity. The earlier a child learns to read, the more he will cultivate the habit and love of reading. Parents as the main pillar in shaping children, have an important role in growing children's interest in reading from an early age. The purpose of this study was to determine the role of parents in fostering children's reading interest and what obstacles parents faced in fostering children's reading interest. This type of research is descriptive qualitative with data collection methods through observation and interviews. The subjects of this study were 10 parents of children aged 5-6 years in Gesik hamlet, Gesikharjo village. The results of this study are the role of parents in growing children's interest in reading is first through parenting, where parenting is influenced by education and parental knowledge about the importance of growing interest in reading from an early age. Second, the role of parents in setting an example for their children. Third, parents have a role in providing literacy-related facilities. Meanwhile, the obstacles faced by parents in cultivating children's reading interest are: 1) Children are more interested in playing mobile games, 2) Children's moods are up and down towards reading activities, 3) Unsupportive environment or friends.